Lentinula edodes Mycelium as Effective Agent for Piroxicam Mycoremediation - Muszyńska, Bożena; Dąbrowska, Monika; Starek, Małgorzata; Żmudzki, Paweł; Lazur, Jan; Pytko-Polończyk, Jolanta; Opoka, Włodzimierz (Frontiers in Microbiology, 2019)
Pollution of the environment with inorganic and organic substances is one of the main problems in the world. For this reason, it is necessary to conduct researches for effective methods of biodegradation of xenobiotics, including drugs whose unmetabolized forms are introduced into the environment, especially into water. One possible solution to this problem may be the use of white rot fungi, such as Lentinula edodes. This is an edible species used in medicine because of its beneficial anti-cancer, hypocholesterolemic, hypotensive, hypoglycemic and antioxidant effects. Due to the fact that the mycelium of L. edodes produces enzymes with oxidizing properties that can degrade xenobiotics. The aim of the work was verification if in vitro cultures of L. edodes can be used for bioremediation of non-steroidal, anti-inflammatory drug: piroxicam. For this purpose, the in vitro culture of L. edodes was derived and the mycelial cultures of this species enriched with piroxicam were analyzed. The biodegradation pathway of piroxicam by L. edodes mycelium was carried out by the UPLC/MS/MS method. The degradation process of piroxicam was found to affect primarily the linker between the thiazine and the piperidine ring, leading to its oxidation and cleavage. Additionally, oxidation of the benzothiazine moiety was observed, leading to hydroxylation and oxidation of the phenyl ring as well as oxidation of the thiazine ring leading to partial or complete removal of the sulfonamide moiety. It seems that the degradation process led finally to 2-hydroxybenozquinone, which may be further oxidized to inorganic compounds. What’s more, concentration of piroxicam in in vitro cultures of L. edodes was not correlated with effectiveness of biodegradation of this compound – on each experimental series, the level of degradation was the same. The results confirm the possibility of using the investigated L. edodes mycelium for remediation of piroxicam.